Форми реалізації екзистенційної свідомості у сучасній монодрамі: сповідь vs скарга - Бортнік, Жанна Іванівна; Bortnik, Zhanna I. (Національний університет «Острозька академія», 2012)
У статті розглядаються сповідь і скарга як форми реалізації екзистенційної свідомості у сучасних українській і російській монодрамах. Здійснено аналіз основних методів та прийомів, які використовують автори для передачі свого бачення екзистенційної проблеми протистояння людини і світу. The confession and appeal as the realization form of the existential consciousness in modern Ukrainian and Russian monodramas are described in the article. The analysis of the main methods and techniques used by monodrama’s authors to transfer their vision of existential problems of human and world opposition is accomplished.
Forms of realization of existential consciousness in modern monodrama:confession vs complaint
Keywords: екзистенційна свідомість; монодрама; сповідь; скарга; персонаж; вибір; соціум; мовленнєвий жанр; existential consciousness; monodrama; confession; appeal; character; Society; speech genre